PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK MENDUKUNG PENGAMBILAN KEPUTUSAN PENERIMAAN PEGAWAI - Kusumawati, Kiki (JURNAL LIMITS, 2023)
Every institution or company will always try to recruit qualified new employees. Employee selection activities are really needed as an effort to improve the performance of the institution or company. The current hiring process is still carried out by convention by inviting applicants to be interviewed, and there are no standard criteria that are prioritized as part of employees who will be recommended to be selected as permanent employees. As a result of the absence of an objective assessment pattern, there is a gap for bargaining in making decisions. Based on the existing problems, it is necessary to strive to develop a method for assessing prospective employees using Simple Additive Weighting (SAW). The results of the assessment using the SAW method can provide alternative solutions for selecting prospective employees according to the established criteria.